Venezuelan Strategy for Agreeing on ALBA in Facing Trade Expansion United States of Latin America - Elia Beatriz Martines (International Journal of Science and Society, 2020)
In 2004 Venezuela and Cuba have agreed on a regional collaboration in Latin America called Alternative Bolivarian Las Americas and abbreviated ALBA. This collaboration is formed as a resistance facing U.S. trade expansion to bring a mission neoliberalism. With the formation of ALBA, Venezuela is the regional co-operation leaders making strategic measures to face Neoliberalism. In 2010 ALBA has had a total of 10 member countries. As a counter hegemony, ALBA also worked in three spaces. In the space of ideas, countries members need complementary principles of solidarity and cooperation to achieve prosperity and equitable regional development. At the institutional space, the idea is then integrated into ALBA.